2013
DOI: 10.1039/c2cp43438e
|View full text |Cite
|
Sign up to set email alerts
|

Proton transfer chains in cold plasmas of H2with small amounts of N2. The prevalence of NH4+

Abstract: The ion-molecule chemistry of the astronomically relevant H

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 51 publications
0
40
1
Order By: Relevance
“…A similar extensive study of H 2 -N 2 plasmas as in the present work was carried out by Carrasco et al 3,27,28 in a DC hollow cathode discharge with comparable plasma conditions. Carrasco et al presented experimental and modeling results for densities of ionic, electron, radical and gas species.…”
Section: Introductionmentioning
confidence: 71%
“…A similar extensive study of H 2 -N 2 plasmas as in the present work was carried out by Carrasco et al 3,27,28 in a DC hollow cathode discharge with comparable plasma conditions. Carrasco et al presented experimental and modeling results for densities of ionic, electron, radical and gas species.…”
Section: Introductionmentioning
confidence: 71%
“…Similar models applied to H 2 +D 2 , H 2 +N 2 and H 2 +Ar discharges can be found in refs. [37][38][39][40]. The model accounts for the main physico-chemical processes: electron impact dissociation and ionization, ion-molecule and ion-ion reactions, neutralization at the wall and heterogeneous chemistry.…”
Section: Modelmentioning
confidence: 99%
“…In the steady state, a small fraction of these hot atoms survives and can be detected either in the line profiles of Balmer emission lines of H atoms [81] or indirectly in the energy resolved mass spectra of H + and O + ions [81][82][83]. However, previous works carried out on this reactor for different gas mixtures at comparable pressures [33,34,[36][37][38][39] have shown that the assumption of a Maxwellian distribution is not a bad approximation for the global kinetics, and we have adopted it here for lack of better information on the actual eedf. The limitations of this approximation should be taken into account in the interpretation of the results.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations